2017
DOI: 10.1089/acm.2016.0309
|View full text |Cite
|
Sign up to set email alerts
|

Framingham Risk Score and Estimated 10-Year Cardiovascular Disease Risk Reduction by a Short-Term Yoga-Based LifeStyle Intervention

Abstract: This yoga-based lifestyle intervention program significantly reduced the CVD risk, as shown by lowered FRS and estimated 10-year CVD risk. Further testing of this promising intervention is warranted in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Medical doctors constantly observed closely and interacted with the participants for the first two weeks at IHC. This allowed us to assess the effectiveness with good compliance, which was noted in our previous studies as well ( 21 24 , 26 , 27 , 29 , 45 ). Also, for better study compliance, we intentionally added one more time point at the 4 th week to evaluate the adherence of the participants to the recommended yoga program at their home based intervention.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…Medical doctors constantly observed closely and interacted with the participants for the first two weeks at IHC. This allowed us to assess the effectiveness with good compliance, which was noted in our previous studies as well ( 21 24 , 26 , 27 , 29 , 45 ). Also, for better study compliance, we intentionally added one more time point at the 4 th week to evaluate the adherence of the participants to the recommended yoga program at their home based intervention.…”
Section: Methodsmentioning
confidence: 83%
“…The intervention is delivered to a group of six to eight participants at a time, allowing them ample time to interact with the experts (medical doctors, yoga experts, and dietitians). The YBLI used in this study has been pretested and published previously (21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…However, the finding was contrary to the study done by R. Yadav et. al [37], where two week of a yoga-based lifestyle intervention can reduce the predicted CVD risk score by 11%. Meanwhile, a previous study on civil servants in South-Western Nigeria using the WHO prediction chart showed that those who were physically inactive had a 2.4 times higher risk in developing CVD as compared to those who were physically active [38].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the workers in health care [15,16] have suggested the increasing role of spirituality specially in the field of gerontology and management of elderly and seriously geriatric patients. It is possible that as humans become matured with age, they leans towards the spiritual [17]. A yoga based life style modification has lead to tangible improvement in the cardiovascular risk factors in a specific cohort and emphasized on role of yoga and spiritual counseling in reducing the health risks through preventive strategies [13].…”
Section: Discussionmentioning
confidence: 99%